1999
DOI: 10.1074/jbc.274.25.17599
|View full text |Cite
|
Sign up to set email alerts
|

Tip60 Is a Nuclear Hormone Receptor Coactivator

Abstract: The androgen receptor (AR) is a member of the nuclear hormone receptor superfamily. Recent work in this field has been focused upon defining the mechanisms of transcriptional control exacted by members of this superfamily. Using a COOH-terminal region of the human AR in a yeast two-hybrid screen, we have identified Tip60 as an AR-interacting protein. In this report, we show that Tip60, which was originally identified as a coactivator for the human immunodeficiency virus TAT protein, can enhance AR-mediated tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 44 publications
(18 reference statements)
3
198
0
1
Order By: Relevance
“…We previously demonstrated that Tip60 interacts directly with the AR and enhances its androgen-induced transcriptional activity (Brady et al, 1999). The distribution pattern and the expression levels of this coactivator in prostate tissue have not yet been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that Tip60 interacts directly with the AR and enhances its androgen-induced transcriptional activity (Brady et al, 1999). The distribution pattern and the expression levels of this coactivator in prostate tissue have not yet been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…FHL2 is an AR-specific co-activator expressed in prostatic epithelium (Muller et al, 2000). We previously identified Tat interactive protein, 60 kDa (Tip60) as an AR coactivator and showed that it potentiates AR transcriptional activity both in vitro and in vivo (Brady et al, 1999). We further demonstrated that Tip60 is a coactivator specific for Class I nuclear hormone receptors, including oestrogen and progesterone receptor (Gaughan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were transfected with the E2F reporter construct (200 ng) (Hofman et al, 2001) together with the b-galactosidase construct (200 ng) (Brady et al, 1999) using FuGENE6 transfection reagent (Roche Diagnostics, Lewes, UK) and treated as indicated in figure legends. Luciferase activity was determined after addition of 50 ml luciferase reagent (Promega, Southampton, UK) using a microplate luminometer (Perkin-Elmer, Beaconsfield, UK).…”
Section: E2f Luciferase Reporter Gene Assaymentioning
confidence: 99%